Prevalência de tempestade elétrica em pacientes chagásicos portadores de cardioversor desfibrilador implantável - Lima , Antônio Malan Cavalcanti (2011)
Background: Chagas’s heart disease remains a major public health problem in Brazil. Sudden death is the leading cause of decease, because of that, the implantable cardioverter defibrillator (ICD) has become an important therapeutic option in this disease. Objective: To define the prevalence and predictors of electrical storm (ES) in patients with Chronic Chagas Heart Disease (CCh) with an ICD. Methods: We retrospectively studied 81 consecutive patients with CCh in whom an ICD was implanted between January 2004 to December 2007, with a mean follow up of 45,9 ± 15 months. Patients were classified into two groups according to the presence of ES episodes. We compared baseline and funcional characteristics. p values less than 0,05 were considered statistically significant. Results: Thirty five patients (43,2%) developed TE during follow up. By univariate analysis, QRS width ≥ 150 ms (p=0,001), previous pacemaker (p=0,001), ventricular tachycardia (VT) for indication of ICD (p=0,001) and cumulative percent ventricular pacing (C%VP) > 40%/80%) were all predictors of TE. However, by multivariate analysis only the indication of ICD for VT (odds ratio (OR) = 9.16, 95% CI: 1.98 to 42.78, p = 0.005) and C%VP > 40%/80% (OR = 6.30, 95% CI: 1.56 to 25.49, p = 0.010) were independent predictors of TE. Conclusion: 1- ES is very frequent in subjects with CCh and ICD; 2- Indication of ICD for VT and C%VP > 40%/80% were independent predictors of TE.